2004
DOI: 10.1002/ceat.200402007
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art and Future Trends in CFD Simulation of Stirred Vessel Hydrodynamics

Abstract: Computational fluid dynamics (CFD) has become a widely used tool for analysing, optimising and supporting the design of mixing processes in stirred vessels. The present contribution gives a brief summary of the methods applied for numerically treating the power input by the impeller, such as empirical methods, the multiple frame of reference approach and unsteady methods using sliding or clicking meshes. Thereafter, recent developments and trends in the numerical computation of single phase flows in stirred ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 24 publications
1
51
0
Order By: Relevance
“…Sommerfeld and Decker (2004) found strong nonphysical accumulation of particles near the bottom wall of the tank if the interparticle collisions were not considered. The importance of particle-particle collisions was emphasized by Derksen (2003).…”
Section: Point-particle Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sommerfeld and Decker (2004) found strong nonphysical accumulation of particles near the bottom wall of the tank if the interparticle collisions were not considered. The importance of particle-particle collisions was emphasized by Derksen (2003).…”
Section: Point-particle Methodsmentioning
confidence: 99%
“…In order to simulate turbulent continuous single-phase flows, three approaches are usually utilized: Reynolds averaged NavierStokes (RANS) simulation, large eddy simulation (LES), and direct numerical simulation (DNS). These approaches and their applications to stirred tanks have been reviewed in detail by Sommerfeld and Decker (2004), Van den Akker (2010), and Joshi et al (2011aJoshi et al ( , 2011b. The present section focuses on the models for simulating the influence of the discrete phase on the continuous phase in comparison with single-phase flows.…”
Section: Models For Continuous Phasementioning
confidence: 99%
“…In the outer region, the relatively small time derivative terms can be neglected. Upon comparing numerical predictions obtained from applying different impeller modeling methodologies, several investigators observed that steady state methods such as MRF can i. provide reasonable predictions to flow field features and power consumption (Jaworski et al, 2001;Bujalski et al, 2002;Kelly & Gigas, 2003;Khopkar et al, 2004;Aubin et al, 2004;Sommerfeld & Decker, 2004;Khopkar et al, 2006), and ii. save about one-seventh of the CPU-time (Brucato et al, 1998).…”
Section: Simulation Of Impeller Rotationmentioning
confidence: 99%
“…Among them, the discretization error is generally the largest one. The analysis of discretization error is even more vital in free surface simulations [1,2] such as bubble in the water, vessel with blood etc. Because cell size and cell shape is always changing which would lead to a varied discretization error.…”
Section: Introductionmentioning
confidence: 99%